Association of survivin splice variants with prognosis and treatment of breast cancer - Pavlidou, A.; Kroupis, C.; Dimas, K. (World J.Clin.Oncol., 2014)
The purpose of this study was the overview of current knowledge regarding the use of survivin and its isoforms in prognosis and treatment of breast cancer. An advanced search of Medline was performed using the following search strategy: "(survivin isoforms) OR (survivin transcript variants) AND (breast cancer) AND (neoplasm OR tumor OR cancer OR carcinoma)". Relevant studies were retrieved and processed thoroughly in order to analyze the related data. Besides wild-type survivin full-length transcript, another six splice variants have been identified. Overexpression of survivin and its isoforms leads to shorter overall and disease-free survival; the transcript variants are correlated with apoptosis and could assist prognosis prediction. It has been proved through numerous studies that inhibiting survivin isoforms might become a promising target of drug therapy of carcinomas. Use of small molecule YM155 could offer new therapy for triple negative breast cancer patients, while, chemotherapy with 5-fluorouracil + epirubicin + cyclophosphamide and Tax-Epi could be guided by survivin splice variants measurements. Survivin transcript variants could become prognostic biomarkers and could provide information about clinical management of patients suffering from breast cancer
DA - 20141210 IS - 2218-4333 (Electronic) IS - 2218-4333 (Linking) LA - eng PT - Journal Article PT - Review